2002
DOI: 10.1046/j.1440-0960.2002.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Diseases of the generative nail apparatus. Part I: Nail matrix

Abstract: Disorders of the generative structures of the nail produce a characteristic set of outcomes. The matrix is the seat of nail development and diseases or insults of this germinative epithelium will tell a story in the signs that unfold in the ensuing nail growth. This story will be influenced by the intensity, duration and extent of this pathology. A method of categorizing changes associated with the generative matrix of the nail will be presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Periungual fibromas may exert pressure on the matrix to cause nail grooves, in much the same way as postulated for digital myxoid cysts 21, 22. However, we and others12 have observed nail grooves in TSC with no visible periungual fibroma.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Periungual fibromas may exert pressure on the matrix to cause nail grooves, in much the same way as postulated for digital myxoid cysts 21, 22. However, we and others12 have observed nail grooves in TSC with no visible periungual fibroma.…”
Section: Discussionsupporting
confidence: 66%
“…It is not a specific finding, however, as longitudinal leukonychia is present inmost patients with Hailey -Hailey disease26, and white streaks together with red streaks are found in Darier disease 22, 27. Longitudinal leukonychiais a relatively uncommon finding in TSC, and its utility in diagnosis must take into account these other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Subungual hyperkeratosis is associated with increased nail plate thickness due to nail bed or hyponychium hyperplasia caused by psoriasis, chronic focal inflammation, trauma to the nail, congenital ichthyosis, and onychomycosis (21)(22)(23). We observed that subungual hyperkeratosis appeared in 27.5% of patients with UC and in 27.3% of patients with CD.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic factors include old age, malnutrition, fever, and severe illness (i.e., mumps, acute febrile tuberculosis, typhoid and chronic nephrosis) (37)(38)(39)(40). Local factors include denervation, including median or ulnar nerve injury (41,42), nail bed injury (43), nail matrix injury (44), sympathetic dystrophy (45), relapsing polychondritis (46), and local infection. Some chemotherapeutic or immunosuppressive agents, such as methotrexate and azathioprine, have also been reported (47) to decrease nail growth.…”
Section: Discussionmentioning
confidence: 99%